KERJA SAMA DI ANTARA SDM PERPUSTAKAAN UNTUK MENUJU LAYANAN PRIMA DAN UNGGUL - Endang Fatmawati (Jurnal Pustaka Ilmiah, 2016)
Internal problems among the human resources in each library must exist. To achieve service excellence and superior library requires cooperation. Cooperation among individuals there is a need of every library. Solid team work is the key to success in managing the library. The practice of cooperation among individuals in the library can be assessed based on aspects of social relations and the exchange of knowledge.